"Being in a group with others who have mental illness makes all the difference": The views and experiences of parents who attended a mental health parenting program. (July 2017) - Coates, Dominiek; Phelan, Ruth; Heap, Joanna; Howe, Deborah
Abstract: Background: The relationship between parental mental illness and poor outcomes in children is well established. While parents with mental illness could benefit from accessing parenting programs, this population tends to be reluctant to do so. To address this need, we developed an adaptation of the Triple P program specific to people with mental illness, and this paper presents the views and experiences of parents who attended this program. The program is a ten week intervention consisting of a six week group parenting program, followed by four weekly home visits. Methodology: This client satisfaction evaluation consists of 18 telephone interviews with program participants as well as feedback from the Triple P Client Satisfaction Questionnaire (CSQ) (N = 116). While this evaluation sought to gain participant feedback on the entire program, the focus was on gaining insight into the usefulness of a modified program specifically for this population, and how the unique components of this modified Triple P program are perceived by the participants. Results: Both the qualitative and quantitative findings indicate high satisfaction with the program, and highlight the value of a parenting program designed specifically for parents with mental illness. In particular, participants stressed that the design of the program was essential to their satisfaction and engagement with the program. Analysis of the interview data identified a number of reasons why participants engaged with this particular parenting program and found it very useful, in particular: being in a group with others with mental illness ; focus on child development and parenting with a mental illness ; and the home visits . Conclusion: This study adds to the limited evidence base specific to parent programs for parents who experience mental illness, and highlights the importance participants attach to sharing the group experience with other parents who also experience mental illness, and the significance of this in facilitating engagement in parenting programs. Highlights: Parents with mental illness benefit from accessing parenting programs but tend to be reluctant to do so. To address this need, we developed an adaptation of the Triple P program specific to people with mental illness. The program is ten weeks consisting of a six week group parenting program, followed by four weekly home visits. Feedback from participants indicates that they valued the design of the program. Participants valued being in a group with others with mental illness and the focus on parenting with a mental illness.